2006
DOI: 10.1364/oe.14.002344
|View full text |Cite
|
Sign up to set email alerts
|

Optical waveguides in Sn2P2S6 by low fluence MeV He+ ion implantation

Abstract: Planar waveguides in nonlinear optical crystals of Sn(2)P(2)S(6) have been produced by He+ ion implantation. The effective indices of the waveguide have been determined and refractive index profiles have been evaluated for the indices along all three principal axes of the optical indicatrix. The depth of the induced optical barrier is n1 = -0.07, n2 = -0.07 and n3 = -0.09 at lambda = 0.633 microm for a fluence Phi = 0.5x10(15)ions/cm(2). Propagation losses for hybrid-n(1) modes are alpha approximately 10dB/cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The thickness of the guiding layer needed for supporting zero-order mode propagation is as small as 157.56 nm when the wavelength of 632.8 nm is used. We have additionally shown that the ellipsometric method reveals some advantages, when compare with the method used in [11], when being applied to the problem of detection of changes in the Sn 2 P 2 S 6 crystal structure appearing as a result of He + ion implantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thickness of the guiding layer needed for supporting zero-order mode propagation is as small as 157.56 nm when the wavelength of 632.8 nm is used. We have additionally shown that the ellipsometric method reveals some advantages, when compare with the method used in [11], when being applied to the problem of detection of changes in the Sn 2 P 2 S 6 crystal structure appearing as a result of He + ion implantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors [11] have not found the lowest energy of the ion beam which is needed for creating single-mode waveguide based on Sn 2 P 2 S 6 crystals. The goal of the present work is to solve this problem with applying an ellipsometric technique.…”
Section: Nm  mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been a lot of activity in recent years on this field. For instance, the traditional ion implantation (i.e., where the waveguides are produced by means of the nuclear collisions) has been used to fabricate waveguides in various materials, such as SnP 2 S 6 (Guarino et al, 2006), KGW (Merchant et al, 2006a;Chen et al, 2008e), KLTN (Gumennik et al, 2005;Ilan et al, 2008), ZnO (Ming et al, 2011), ZnWO 4 (Zhao et al, 2010a), Nd:YAG , Nd:YLiF 4 (Tan et al, 2007b), Nd:…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the results on the optical activity in Sn 2 P 2 S 6 crystals are still absent, though the gyration effect can essentially affect at least the process of photorefractive diffraction. On the other hand, a principal possibility has been recently shown for realization of planar waveguides based on Sn 2 P 2 S 6 [10], thus suggesting that the crystals can be utilized in the integrated optics. Up to now, electrogyration effect is not used in practical optoelectronics, whereas the angles of electrically induced optical rotation accessible at high operating voltages are quite small for the most of materials.…”
Section: Introductionmentioning
confidence: 99%